1989
DOI: 10.1123/apaq.6.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics of Wheelchair Design: A Prerequisite for Optimum Wheeling Conditions

Abstract: A review of wheelchair research within the scope of the wheelchair as a means of daily ambulation is presented. The relevance of a combined biomechanical and physiological research approach is advocated for enhancing the body of knowledge of wheelchair ergonomics, that is, the wheelchair/user interaction in relation to aspects of vehicle mechanics and the user’s physical condition. Results of experiments regarding variations in the wheelchair/user interface stress the possibilities of optimization in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Although the participants were blinded to their performance at the first study visit, they were able to recall their reached stage at the first study visit themselves due to the audio signals emitted throughout the SRiT. Furthermore, the influence of the wheelchair properties and individually adjusted wheelchair designs, both important factors in wheelchair mobility, 9,10 was not examined. Together with propulsion skills, these factors might influence SRiT performance.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Although the participants were blinded to their performance at the first study visit, they were able to recall their reached stage at the first study visit themselves due to the audio signals emitted throughout the SRiT. Furthermore, the influence of the wheelchair properties and individually adjusted wheelchair designs, both important factors in wheelchair mobility, 9,10 was not examined. Together with propulsion skills, these factors might influence SRiT performance.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Within-cycle parameters have also been described frequently in the literature [4,11,[15][16][17][18][19][20][21]. Among these studies, Vanlandewijck et al was particularly interested in wheelchair basketball propulsion [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Very little information is available concerning the untrained female paraplegic, the untrained male paraplegic and the quadriplegic. (Hooker and Wells, 1989;van der Woude et al, 1989;Wicks et al, 1983). Several researchers (Figoni 1984;Gass and Camp, 1979;Van Loan et al, 1987;and Wicks et al, 1983) have suggested that VOz max is related to the level of spinal injury, but their data did not show such a relationship.…”
mentioning
confidence: 96%